Improving Students' Learning Outcomes in Non-Numerical Pattern Recognition Through Problem-Based Learning Assisted by a Pictorial Pattern Board in Elementary School - Anastasya Kurnia Ahmad; Irvin Novita Arifin; Nur Sakinah Aries; Isnanto; Hadi Yamin Assel (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2026)
This study aimed to improve the learning outcomes of first-grade elementary school students in learning non-numerical patterns through the implementation of Problem-Based Learning (PBL) assisted by a Pictorial Pattern Board at SDN 7 Talaga Jaya. This study employed Classroom Action Research (CAR) based on the Kemmis and McTaggart model, which was conducted in two cycles, each consisting of planning, implementation, observation, and reflection. The participants were 20 first-grade students. Data were collected through classroom observations, learning achievement tests, and documentation, and were analyzed using descriptive quantitative and qualitative approaches. The success criterion was established as at least 80% of students achieving the minimum learning mastery. The findings revealed a substantial improvement in students' learning outcomes. Learning mastery increased from a low baseline to 70% (14 students) in Cycle I and further improved to 90% (18 students) in Cycle II. These findings indicate that the implementation of Problem-Based Learning assisted by a Pictorial Pattern Board effectively improved students' learning outcomes in non-numerical pattern learning among first-grade students at SDN 7 Talaga Jaya.